MUC551 : Jingle production / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course examines the process of producing commercial from client meeting agency to composer synchronizing their music with offline cut. Students will get hands-on experience from preparing timings and crafting hook to writing music for one of these 3 categories: jingle songs, music background for broadcasting VO, or underscoring TVC. Lecturer shares his/her successes in previous projects and his/her past mistakes as students build their own skills in composing and producing commercial and in finding, communicating with, and negotiating with agencies and clients. Students will have opportunity to work at a recording studio or post-production house for their final project, and hopefully, bring home an industrial standard demo.